2020
DOI: 10.47524/jlst.v2i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Social media as platforms for information sharing among librarians in Anambra State, Nigeria

Abstract: The global trend on the use of social mediahas enhanced professional information sharing andnetworking. This development has created spaces forgroupsthat determine who gets informed, updated, inspiredand connectedas members. The librarians in Nigeria are not left out in this strategic phenomenon. This paper evaluated the different social media platformsused by librarians in Nigeria, thebenefits and the challenges. It was an expository researchthat employedfocus group discussion. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The good thing is that, when it happens, there are always a few members who will quickly condemn the post and call on the administrator of the group to act. The study by Osuchukwu and Nguzoro (2019) mentioned that one major challenge with the use of social media platforms is that some members do not conform to the rules and regulations of the group, thereby causing unwanted rancour and friction. For instance, posting of unnecessary copy-and-paste as well as religious or business advertisements can cause unwanted rancour and friction.…”
Section: Obeying Rules Governing the Whatsapp Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…The good thing is that, when it happens, there are always a few members who will quickly condemn the post and call on the administrator of the group to act. The study by Osuchukwu and Nguzoro (2019) mentioned that one major challenge with the use of social media platforms is that some members do not conform to the rules and regulations of the group, thereby causing unwanted rancour and friction. For instance, posting of unnecessary copy-and-paste as well as religious or business advertisements can cause unwanted rancour and friction.…”
Section: Obeying Rules Governing the Whatsapp Groupsmentioning
confidence: 99%
“…With the increased importance of technology in society, the use of WhatsApp is gaining recognition as a valuable information-sharing tool (Osuchukwu and Nguzoro, 2019;Semode et al, 2017). WhatsApp is an instant messaging app, invented in 2009 by Brian Acton and Jan Koum (Purkayastha and Chanda, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These platforms allow people to engage, interact and communicate with one another instantly irrespective of their location. From platforms like Facebook and Twitter, to Instagram and LinkedIn social media has transformed how people connect and share information (Alhabash & Ma, 2017;Blank & Lutz, 2017;Chu, 2017;Osuchukwu & Nguzoro, 2020;Sharma, 2022). Statista (2021) report indicated that in 2020 there were 3.6 billion users, on media with a projected rise to 4.41 billion by 2025.…”
Section: Introductionmentioning
confidence: 99%